Enhanced immunity in a mouse model of malignant glioma is mediated by a therapeutic ketogenic diet. Issue 1 (December 2016) - Lussier, Danielle; Woolf, Eric; Johnson, John; Brooks, Kenneth; Blattman, Joseph; Scheck, Adrienne
Abstract Background Glioblastoma multiforme is a highly aggressive brain tumor with a poor prognosis, and advances in treatment have led to only marginal increases in overall survival. We and others have shown previously that the therapeutic ketogenic diet (KD) prolongs survival in mouse models of glioma, explained by both direct tumor growth inhibition and suppression of pro-inflammatory microenvironment conditions. The aim of this study is to assess the effects of the KD on the glioma reactive immune response. Methods The GL261-Luc2 intracranial mouse model of glioma was used to investigate the effects of the KD on the tumor-specific immune response. Tumor-infiltrating CD8+ T cells, CD4+ T cells and natural killer (NK) cells were analyzed by flow cytometry. The expression of immune inhibitory receptors cytotoxic T-lymphocyte-associated protein 4 (CTLA-4) and programmed death 1 (PD-1) on CD8+ T cells were also analyzed by flow cytometry. Analysis of intracellular cytokine production was used to determine production of IFN, IL-2 and IFN- in tumor-infiltrating CD8+ T and natural killer (NK) cells and IL-10 production by T regulatory cells. Results We demonstrate that mice fed the KD had increased tumor-reactive innate and adaptive immune responses, including increased cytokine production and cytolysis via tumor-reactive CD8+ T cells. Additionally, we saw that mice maintained on the KD had increased CD4 infiltration, while T regulatory cell numbers stayed consistent. Lastly, mice fed the KD had a significant reduction in immune inhibitory receptor expression as well as decreased inhibitory ligand expression on glioma cells. Conclusions The KD may work in part as an immune adjuvant, boosting tumor-reactive immune responses in the microenvironment by alleviating immune suppression. This evidence suggests that the KD increases tumor-reactive immune responses, and may have implications in combinational treatment approaches.